Understanding Children’s Experiences of Violence in Andhra Pradesh and Telangana, India: Evidence from Young Lives - Morrow, V; Singh, R (UNICEF Office of Research, 2016)
This paper explores children’s accounts of violence in Andhra Pradesh, India, and the ways in which factors at the individual, family, community, institutional and society levels affect children’s experiences of violence. The paper analyses cross-sectional survey data and case studies from longitudinal qualitative data gathered over a seven-year period, from Young Lives. The paper is divided into four sections – a brief background section, study design and methods, findings from the survey, and findings from case studies. Large proportions of children experience violence (mostly physical punishment and emotional abuse) within their families, at school and, to some extent, within their communities. The findings demonstrate how children’s experiences of violence change with age and that gender differences within this dynamic process are very distinct. The paper reveals that a child’s disapproval of violence does not necessarily influence behaviour in later life, confirming the need for interventions to prevent and tackle violence as children grow up.